We need a global language rights movement: confronting the global language crisis with insights from social movement studies - Gerald Roche (Global Social Challenges Journal)
Since the late 1980s, academics and activists have been drawing attention to a slow-moving global crisis: the ongoing destruction of global linguistic diversity. Despite this attention, language loss has proceeded unabated, and conservative estimates now suggest that around half the world’s languages will no longer be in use by the end of this century. In this provocation, I argue that only a global mass movement has the capacity to change the course of this crisis. I furthermore argue that a rights-based approach, centred on language rights, is our best bet for organising such a movement. Drawing on social movement studies, and my own experience as a language rights researcher and advocate, I explore three key areas where language rights provide the foundations for a mass movement in defence of linguistic diversity. First, I look at how language rights provide a discursive frame that resonates with other movements and clarifies the problem that needs to be addressed. Second, I look at how the concept of language rights can help recruit individuals and organisations into a mass movement and sustain their involvement in the cause. Third, I discuss how language rights provide a basis for effective collective action. In the conclusion I briefly discuss some of the challenges that will need to be overcome in forming a global mass movement for language rights.